Kajian Kematian Ibu berdasarkan Kategori ANC, Kategori Risiko Tinggi dan Rujukan Kasus Risiko Tinggi di Kabupaten Sumba Timur Tahun 2011-2015 - Mariana Ngundju Awang (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2017)
Introduction: The maternal mortality rate is also one of the targets set in the millennium development goal of the fifth goal of improving maternal health where the target to be achieved until 2015 is to reduce to ¾ the risk of maternal mortality and 2/3 of infant mortality. The three main factors causing maternal and infant deaths; 1). Medical factors (direct and indirect), 2). Service system factors (antenatal care system, delivery service system and post-natal service system and child health services); and 3). Economic factors, socio-cultural and community participation (lack of recognition of problems, late decision-making, lack of access to health services, gender mainstreaming, and community participation in maternal and child health) (Nurrizka & Saputra 2013). The region with the highest MMR in Indonesia is East Nusa Tenggara. East Nusa Tenggara is one of the 5 provinces contributing the greatest number of maternal deaths in addition to West Java, Central Java, East Java and North Sumatra. Maternal mortality in East Nusa Tenggara shows a fluctuating trend. East Sumba regency is one of the areas in East Nusa Tenggara that has 21 health centers. AKI in East Sumba Regency is still relatively high based on the annual report of East Sumba District Health Office for the last five years (2011-2015). The maternal mortality rate in East Sumba is one of the highest in East Nusa Tenggara. Maternal mortality rates have fluctuated over the last five years from 2011 to 2015 - 20 - 2 - 15 - 19 and 11 maternal deaths (East Sumba District Health Office 2015). Research Objectives To identify maternal mortality risk factors based on the frequency of ANC, high-risk category and high-risk case referral in East Sumba Regency 2011-2015. The benefit of Research: The type of research used is observational analytic research, with design or case-control study design (case-control study). Population and Sample are cases of maternal and infant mortality in 2011 - 2015, control is mother and infant who survived in labor process year 2011 - 2015. Results: The high or very high-risk category of the mother during pregnancy is one of the risk factors that cause the pregnant woman to regularly perform ANC and regularity of ANC frequency to reduce maternal mortality in East Sumba Regency in 2011 - 2015. Case referral system from Public Health Center/home Sick to the referral hospital is a risk factor that reduces maternal mortality in East Sumba regency 2011 - 2015 with the result of regression logistic test at 95% CI p-value 0.05 obtained OR value more than 1. Conclusion: Frequency of regular ANC, Planning of birth and referral the planned and timely cases of pregnant and maternity in pregnant women with high and very high-risk categories are risk factors for maternal mortality in East Sumba Regency in 2011 - 2015.